You are here:

# Algebra/Solve for X

Question
(X/4)=(-X/2)-1

X/4 and -X/2 are fractions.

Multiply both sides of the equation by 4.
This gives 4(x/4) = 4(-x/2) - 4.

4(x/4) is the same as 4x/4 = x.
4(-x/2) is  the same as -4x/2 = -2x.

This gives x = -2x - 4.

Add 2x to both sides, giving 2x+x = -4.
This is the same as 2x+1x = -4.
Adding the x terms gives 3x = -4.
Dividing by 3 gives x = -4/3.

Putting that back in to check gives (-4/3)/4 = (4/3)/2 - 1.

If -4/3 is divided by 4, the result is -1/3.

If 4/3 is divided by 2, the result is 2/3.
When 1 is subtracted from 2/3 the answer is -1/3.

As can be seen, both sides evaluated to -1/3, so that answer is correct.

Algebra

Volunteer

#### Scott A Wilson

##### Expertise

Any algebraic question you've got. That includes question that are linear, quadratic, exponential, etc.

##### Experience

I have solved story problems, linear equations, parabolic equations. I have also solved some 3rd order equations and equations with multiple variables.

Publications
Documents at Boeing in assistance on the manufacturiing floor.

Education/Credentials
MS at math OSU in mathematics at OSU, 1986. BS at OSU in mathematical sciences (math, statistics, computer science), 1984.

Awards and Honors
Both my BS and MS degrees were given with honors.

Past/Present Clients
Students in a wide variety of areas since the 80's; over 1,000 of them have been in algebra.